Half‐Fused Diketopyrrolopyrrole‐Based Conjugated Donor–Acceptor Polymer for Ambipolar Field‐Effect Transistors. (20th March 2020) - Shi, Dandan; Liu, Zitong; Ma, Jing; Zhao, Zhiyuan; Tan, Luxi; Lin, Gaobo; Tian, Jianwu; Zhang, Xisha; Zhang, Guanxin; Zhang, Deqing
Abstract: A novel building block, denoted as half‐fused diketopyrrolopyrrole (DPP) (9‐(3‐octadecylhenicosyl)‐8‐(thiophen‐2‐yl)‐7 H ‐pyrrolo[3, 4‐ a ]thieno[3, 2‐ g ]indolizine‐7, 10(9 H )‐dione), in which one of the flanking thiophene units is fused to one of the DPP rings via a carbon‐carbon double bond at the N‐position is reported. The half‐fused DPP is successfully utilized as an electron acceptor to prepare the conjugated donor–acceptor polymer PTFDFT, which exhibits ambipolar semiconducting behavior in ambient air. Theoretical calculations and absorption spectral studies show that the backbone of PTFDFT is more planar compared to the reference polymer with conventional DPP units. As a result, PTFDFT shows a narrow bandgap and low lowest unoccupied molecular orbital level. The more planar backbone with fewer side chains favors the dense packing of the polymer chains of PTFDFT with a short π–π stacking distance (3.49 Å). Grazing‐incidence wide‐angle X‐ray scattering data further confirm the predominant edge‐on packing mode of the PTFDFT polymer chains on the substrate. As expected, the PTFDFT thin film shows excellent ambipolar semiconducting properties under ambient conditions, reaching 2.23 and 1.08 cm 2 V −1 s −1 for the n‐ and p‐channels, respectively. In addition, complementary‐like inverter with gain value as high as 141 is successfully constructed using the PTFDFT thin film. Abstract : A novel half‐fused diketopyrrolopyrrole‐based conjugated donor–acceptor polymer is identified for use as high‐performance, ambipolar field‐effect transistors and high‐gain inverters.